Study on Ratio of Jerbung Shrimp Waste Powder (Fenneropenaeus Merguiensis de Man) and Purple Yam Starch in the Production of Bioplastics: Yam starch bioplastics - Widiyawati, Sri; Nazarudin, Nazarudin; Ulyarti, Ulyarti (PUI BiGME Universitas Jambi, 2024)
This research aims to determine to study the ratio of Jerbung shrimp waste powder and purple yam starch in the production of bioplastics. This research used a Completely Randomized Design (CRD) with 5 levels of ratio of jerbung shrimp waste powder and purple yam, namely 0:5; 0.5:4.5; 1:4; 1.5: 3.5 and 2:3. Each treatment was repeated 3 times to obtain 15 experimental units. The results showed that the ratio of Jerbung shrimp waste powder and starch had a significant effect on tensile strength, elongation, thickness, water resistance and WVTR. The best bioplastic characteristics was best produced using the ratio 0.5:4.5 with tensile strength of 18.17 N/mm2, elongation of 68.06%, thickness of 0.35 mm, water resistance of 75.15 %, WVTR 22.29 g/m2.hour.